The Impact of Al Islam and Muhammadiyah Development on Integrity, Obedience, and Involvement in Muhammadiyah Organizations - Safi'i, Imam; Tarmini, Wini (SUHUF, 2023)
This study aims to describe the responses of alumni of the Indonesian Language Education Study Program regarding the impact of fostering Al Islam and Kemuhammadiyahan on integrity, religious observance, and the commitment of graduates to be actively involved in the Muhammadiyah organization. The method used in this research is the survey method. Respondents in this study were alumni of the 2020/2021 Indonesian Language Education Study Program. The number of alumni who were successfully traced was 76. The study results showed that 69.74% of alumni thought that Islamic and Muhammadiyah-style coaching greatly impacted building integrity. As many as 75% of alumni believe that the guidance of Al Islam and Kemuhammadiyahan has an influence on religious observance. The high impact of fostering Al Islam and Kemuhammadiyahan on the integrity and observance of the worship of the alumni has not been directly proportional to the interest in the involvement of alumni in the Muhammadiyah organization. As many as 51.32% of alumni have not been involved in the Muhammadiyah organization.